Postcolonial contraventions: Cultural readings of race, imperialism and transnationalism - Chrisman, Laura (Manchester University Press, 2003)
Laura Chrisman's Colonial Discourse and Postcolonial Theory: A Reader was published in 1993. It quickly became a landmark of postcolonial studies. This timely new book offers insights into the field she helped establish. Both polemical and scholarly, Postcolonial contraventions is challenging in its analysis of black Atlantic studies, colonial discourse analysis and postcolonial theory. She provides important new paradigms for understanding imperial literature, Englishness, and black transnationalism. Her concerns range from the metropolitan centre of Conrad's Heart of Darkness, to fatherhood in Du Bois's The Souls of Black Folk; from the marketing of South African literature to cosmopolitanism in Chinua Achebe; from utopian discourse in Benita Parry to Frederic Jameson's theorisation of empire. Chrisman also critically engages with postcolonial intellectuals Paul Gilroy, David Lloyd, Anne McClintock, Edward Said, Gayatri Spivak and Robert Young, uncovering conservatism from unexpected quarters. The book joins a growing chorus of materialist voices within postcolonial studies, and addresses an urgent need for greater attention to the political, historical and socio-economic elements of cultural production. This book will be of interest to students, researchers and teachers of postcolonial studies, theory and literature; black diaspora and Atlantic studies; imperialism and Victorian literature of empire, and British literature of the nineteenth century.